2016
DOI: 10.1515/pomr-2016-0070
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design and Numerical Simulation on Fish-Like Flexible Hydrofoil Propeller

Abstract: Hydrofoil is widely used in underwater vehicle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The risk research of water conservancy PPP project is mainly of qualitative description. There is a certain gap between the existing evaluation model and the actual project operation application at the present stage (Shen et al 2017, Xue et al 2016. The calculation process is complicated, and the evaluation result is not clear, which makes the risk evaluation of water conservancy PPP project still immature.…”
Section: Introductionmentioning
confidence: 99%
“…The risk research of water conservancy PPP project is mainly of qualitative description. There is a certain gap between the existing evaluation model and the actual project operation application at the present stage (Shen et al 2017, Xue et al 2016. The calculation process is complicated, and the evaluation result is not clear, which makes the risk evaluation of water conservancy PPP project still immature.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Liu (2014) constructed a bionic hydrofoil based on the geometric characteristics of an owl, which effectively improved the lift and drag characteristics of the hydrofoil and revealed the characteristics of the sound source. Xue et al (2016) regarded fish as imitation organisms and designed a fin-peduncle propulsion mechanism in accordance with their shape, which improved the propulsion efficiency of hydrofoil propellers. In the above research report, when obtaining the surface information of an organism, acquiring an accurate bionic physical model through curve-fitting technology is a critical step.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we observed that the wings/fins of birds/ fish are simply modelled as a rigid foil to discuss bionic propulsion. However, these wings/fins are flexible and it is necessary to discuss the effect of that flexibility on the propulsive characteristics and vortex structure of the foil [23][24][25]. Heathcote and Gursul [26] experimentally measured the thrust and efficiency of a heaving flexible teardrop/flat plate at Reynolds numbers of 9,000 to 27,000.…”
Section: Introductionmentioning
confidence: 99%